KAJIAN EKOLOGI, KEANEKARAGAMAN JENIS DAN POTENSI POHON DI PEKARANGAN (STUDI KASUS DI DESA KEBAK, JUMANTONO, KARANGANYAR) - Arief Susanto; Endang Setya Muliawati; Djoko Purnomo (Universitas Sebelas Maret, 2015)
Homegarden is one alternative that multipurpose agricultural land to cope with reduced land resources. This study aimed to determine the characteristics of the ecology, species diversity and potential of trees in the homegarden that is useful in further development. The research had been conducted in June to August 2011 in the Kebak Village, Jumantono District, Karanganyar Regency with a altitude of 330 meters above sea level and soil type alvisol. This experiment used survey methods with observation unit is divided into three categories based on the size of the homegarden: narrow (<700 m2), medium (700-900 m2) and large (> 900 m2). Observed variables include three aspects: biological variables (type and number of trees, tree height, trunk diameter and canopy area), physical variables (analysis of soil, microclimate homegarden, macroclimate and physiographic land) and analysis of the vegetation (density, frequency, dominance, relative density, relative frequency, relative dominance, importance value index and the index of species diversity). Kebak village had been 40 species of trees are divided into fruit trees, timber, vegetable producers, growers and others. The results showed indicate that the type of fruit tree had the largest of 20 species by the reached 142 tree to rambutan tree. Spacious homegarden area had the highest type and number of trees as well as the highest species diversity index.